Soyasaponins from Zolfino bean as aldose reductase differential inhibitors. (1st January 2019) - Balestri, Francesco; De Leo, Marinella; Sorce, Carlo; Cappiello, Mario; Quattrini, Luca; Moschini, Roberta; Pineschi, Carlotta; Braca, Alessandra; La Motta, Concettina; Da Settimo, Federico; Del-Corso, Antonella; Mura, Umberto
Abstract: Seven triterpenoid saponins were identified in methanolic extracts of seeds of the Zolfino bean landrace ( Phaseolus vulgaris L.) by HPLC fractionation, revealing their ability to inhibit highly purified human recombinant aldose reductase ( h AKR1B1). Six of these compounds were associated by MS analysis with the following saponins already reported in different Phaseolus vulgaris varieties: soyasaponin Ba (V), soyasaponin Bb, soyasaponin Bd (sandosaponin A), soyasaponin αg, 3- O -[R-l -rhamnopyranosyl(1 → 2)- α -d -glucopyranosyl(1 → 2)- α -d -glucuronopyranosyl]olean-12-en-22-oxo-3 α, -24-diol, and soyasaponin βg. The inhibitory activity of the collected fractions containing the above compounds was tested for h AKR1B1-dependent reduction of both l -idose and 4-hydroxynonenal, revealing that some are able to differentially inhibit the enzyme. The present work also highlights the difficulties in the search for aldose reductase differential inhibitors (ARDIs) in mixtures due to the masking effect on ARDIs exerted by the presence of conventional aldose reductase inhibitors. The possibility of differential inhibition generated by a different inhibitory model of action of molecules on different substrates undergoing transformation is also discussed.